1999
DOI: 10.1002/(sici)1096-9071(199903)57:3<252::aid-jmv7>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genotypes of a nonenveloped DNA virus associated with posttransfusion non-A to G hepatitis (TT virus) in plasma and peripheral blood mononuclear cells

Abstract: TT virus (TTV) is a nonenveloped, single-stranded DNA virus with little sequence homology to known viruses, and associated with elevated transaminase levels in the patients with posttransfusion hepatitis of unknown etiology. The DNA of TTV was detected, by semi-nested polymerase chain reaction, in peripheral blood mononuclear cells (PBMC) from the 30 healthy individuals with circulating virus in plasma. A sequence of 222 bases was determined on 6-10 TTV DNA clones each from plasma and 6 clones -each from PBMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 38 publications
6
53
0
Order By: Relevance
“…TTV has previously been shown to circulate in blood closely associated with PBMC as well as free virions (13,25,28). In eight patients of Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…TTV has previously been shown to circulate in blood closely associated with PBMC as well as free virions (13,25,28). In eight patients of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Suggestions that the liver is a major site of replication (26) have been questioned (9). On the other hand, the observation that TTV is consistently found associated with extensively washed peripheral blood mononuclear cells (PBMC) and grows in cultured phytohemagglutinin-stimulated PBMC (13,25,27) is evidence for a more or less pronounced tropism for lymphoid tissues.…”
mentioning
confidence: 99%
“…The other important factor regarding TTV evolution is the capability of multiple genotypes and genetic variants (see above) to persist for a long period in one infected person (3,21,29,31). One study, for example, showed that the nucleotide sequence of TTV genotypes 1 and 2 could be detected over a 15-month follow-up period without any alterations (3).…”
Section: Vol 74 2000mentioning
confidence: 99%
“…To date, more than 16 genotypes separated by more than 30% divergence at the nucleotide level have been described (6,7,14,16,18,22), incorporating three hypervariable regions (13). Understanding the origins of such diversity is a fundamental problem in virology.…”
mentioning
confidence: 99%